Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division terhadap Kemampuan Pemecahan Masalah Matematika Siswa di Sekolah Dasar - Fida Rahmantika Hadi (STKIP Taman Siswa Bima, 2023)
This research aims to investigate the positive impact of implementing the cooperative learning model of STAD type on students' mathematical problem-solving abilities. The research method used is a Quasi-Experiment with a Pretest-Posttest design and a Non-Equivalent Control Group. The study population comprises all fourth-grade students in primary schools in the Madiun, with a sample of 26 students in the experimental group and 21 students in the control group. Data were collected through pretest and posttest assessments and analyzed using the Mann-Whitney test. The hypothesis analysis results indicate that the mathematical problem-solving abilities of students in the experimental group, which applied the STAD cooperative learning model, significantly outperformed the abilities of students in the control group receiving conventional instruction. The conclusion of this research is that the STAD cooperative learning model has a significant positive impact on students' mathematical problem-solving abilities